The relationship between formal and informal care among Chinese older adults: based on the 2014 CLHLS dataset - Wenyi LIN (BMC, 2019)
Abstract Background The substitute or complementary effect of formal care on informal care service used by the elderly has been tested in Western countries. However, this effect is excluded from the discussion in the Chinese context. The identification of the relationship between informal care and formal care may imply different directions in policy-making. Thus, this study contributes to understanding the relationship between informal care and formal care among Chinese older adults. Methods Using the dataset from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) in 2014, this study uses regression models and instrumental variable (IV) method to examine the impact of formal care on informal care. Results The results primarily show that formal care does not substitute informal care among Chinese older adults. In fact, formal care is a supplement to informal care in China. Conclusion It is expected that informal care will become less available in the future in China. Thus, policymakers should be concerned about the underdevelopment of formal care for the elderly in China.